A qualitative interview study exploring the experiences of pain specialists on prescribing opioids for chronic non-cancer pain - Thomas F. Kallman; Emmanuel Bäckryd; Anne Söderlund Schaller (Scientific Reports)
Abstract Opioid prescribing for patients with chronic non-cancer pain is common despite issues associated with long-term efficacy, functional improvement, and safety. Pain specialists assess many patients with chronic non-cancer pain, but their experiences of this situation are not well represented in prior qualitative research. The aim of this study was to explore pain specialists’ experiences of prescribing opioids to patients with chronic non-cancer pain. We adhered to the Consolidated Criteria for Reporting Qualitative Research guidelines. Pain specialists in Sweden were recruited by purposive and snowball sampling. Participants were digitally interviewed, audio and video were recorded, and interviews translated verbatim. Data was analyzed through manifest inductive content analysis. Twenty pain specialists were interviewed. Qualitative content analysis revealed that the pain specialists’ experiences were represented by two main categories: (1) Navigating the doctor-patient relationship, and (2) Challenges and opportunities when prescribing opioids. The first main category describes the relational demands associated with opioid prescribing and includes communication, conflicts, managing expectations, and the emotional and ethical aspects of prescribing opioids. The second main category describes handling complexity and heterogeneity, organizational aspects, and the doctor’s due diligence when prescribing opioids. Our results offer new insights into pain specialists’ experiences of prescribing opioids for chronic non-cancer pain, offering health care professionals guidance for responsible opioid prescribing. Pain specialists highlight the need for structured pain assessments and identify system-level improvements, such as allocating sufficient time, enabling team-based care, and continued education initiatives, to support safe opioid use in health care.